Superficial temporal artery access for percutaneous coronary artery stenting during the COVID-19 pandemic: a case report - Csavajda, Ádám (Eur Heart J Case Rep, 2020)
BACKGROUND: The COVID-19 pandemic creates new challenges for healthcare, including invasive cardiology. CASE SUMMARY: We discuss the case of a 65-year-old man who presented with non-ST segment elevation myocardial infarction combined with bilateral pneumonia. The patient had known severe iliac artery lesions with prior interventions and bilateral subclavian artery occlusions. After unsuccessful femoral artery access, the diagnostic angiography and the right coronary artery percutaneous coronary intervention were successfully performed from ultrasound-guided lower superficial temporal artery access. DISCUSSION: We showed that superficial temporal access can be used as an alternate access site for diagnostic coronary angiography and intervention when standard wrist and femoral access sites are not readily accessible.